Spanish-Dementia Knowledge Assessment Scale (DKAS-S): Ecuadorian validation and comparison among Spanish health students - A., Carnes-Vendrell; E., Barallat-Gimeno; B., Lara; A., Lladó; MA, Escobar-Bravo; GG, Reivan-Ortiz; EA, Maxi-Maxi; PC, Martínez-Suárez; AA, Ramírez-Coronel; G., Piñol-Ripoll (BMC geriatrics, 2023)
Introduction Alzheimer’s disease (AD) is the most frequent cause of cognitive impairment. Improving knowledge of dementia management through health education for health professionals can improve clinical and community care in home and specialist settings. It is important to guarantee good dementia knowledge in health students, and it is necessary to evaluate it with a good standardized tool. The aim of the current study was to assess the psychometric properties of the DKAS-S with cohorts of Ecuadorian health students, to compare these results with a former validation in Spanish health students and to analyse the level of knowledge according to different variables. Methods We performed a cross-sectional study to assess the validity, reliability and feasibility of the DKAS-S by comparing two different cohorts of health students (nursing and psychologists). Results A total of 659 students from Spain ( n = 233) and Ecuador ( n = 426) completed the DKAS-S (mean age 24.02 (6.35) years old), and 52.80% were nursing students. The DKAS-S showed good internal consistency in the Ecuadorian cohort (Cronbach’s α = 0.76). No significant difference was found between Spanish and Ecuadorian students ( p = 0.767) in the global scale score, but there were differences in some subscales. Psychologist students scored significantly higher on the global scale than nursing students (32.08 (9.51) vs. 27.49 (7.15); p < 0.001)). Students with a family history of cognitive impairment scored higher on the global scale, and those who had contact with people with dementia obtained better results on the global scale. Conclusions We confirmed that the DKAS-S is an adequate and useful instrument to measure levels of knowledge about dementia among health students in Spanish-speaking communities. It is a reliable and valid measure with good psychometric properties. Understanding health students’ knowledge about dementia will allow better adaptation of academic plans to train better health professionals.